PSoC-based embedded system for the acquisition of EMG signals with Android mobile device display - Almeida M., Javier Andrés; Rodríguez Q., Mayra Alejandra; Rubiano L., Juan Sebastián (TECCIENCIA, 2015)
In this study, we present the development of an embedded system for the acquisition and processing of Surface Electromyography (EMGs) signals, using Cypress Semiconductor’s PS0C technology. With this technology, we achieved a decrease in resource consumption during implementation and in the usage of passive components that are usually part of the filtering, conditioning and acquisition stage, thus allowing for the development of a lightweight portable device. We also developed an application for the Android operating system, where EMG signals sent by Bluetooth can be displayed on a mobile device such as a smartphone or tablet.